2
$\begingroup$

Assume that $f : X \rightarrow Y $ is surjective. Show that $f(A^c) = (f(A))^c \ \forall A\subset X$ iff $f$ is also injective.

So I tried starting with the right implication $\Rightarrow$

Since $f$ is surjective we know that every $ y\in Y$ corresponds to some $x\in X$. Then we want to prove that this $x \in X $ is at most one.

I came to the conclusion that since $f(A^c) = (f(A))^c \ \Leftrightarrow f(A) \cap (f(A))^c = \emptyset \ \Rightarrow \not\exists x \in A $ s.t $f(x) \in (f(A))^c$ and $\not\exists x \in A^c $ s.t $f(x) \in f(A)$. Now i want to prove that if there $\exists (f(x_1),\ f(x_2)) \in A$ s.t $ f(x_1)=f(x_2)$ then $x_1=x_2$ and of course $\exists (f(x_1),\ f(x_2)) \in A^c$ s.t $ f(x_1)=f(x_2)$ then $x_1=x_2$

But here I have troubles.

$\endgroup$
  • 1
    $\begingroup$ Hint: Remember you are assuming $f(A^C) = (f(A))^C$ for all subsets of $X$. This includes the case where $A = \{x_1\}$. $\endgroup$ – Browning Jan 29 '16 at 22:41
2
$\begingroup$

If $f(A^c) = (f(A))^c \ \forall A\subset X,$ in particular, given $x\in X$ it is $f(\{x\}^c) = \{f(x)\}^c.$ That is, if $y\not \in \{x\}$ ($y\ne x$) then $f(y)\in \{f(x)\}^c$ (that is, $f(y)\ne f(x)$). This shows that $f$ is injective.

The converse implication must be easy as $f$ is bijective.

$\endgroup$
  • $\begingroup$ "$y \not \in \{x\}$"then shouldnt $y \in \{x\}^c$ and hence $f(y) \in \{f(\{x\}^c)$? But if $y_1, \ y_2 \not \in \{ x \}$ then $f(y_1), \ f(y_2) \in \{f(x)\}^c$ How does one know that $f(y_1) \not = f(y_2)$ ? $\endgroup$ – Olba12 Jan 29 '16 at 22:54
  • $\begingroup$ We are showing that for any $x$ there is no $y$ with $f(x)=f(y).$ Note that $x$ can be any element of $X.$ Thus we can conclude that $f$ in injective. $\endgroup$ – mfl Jan 29 '16 at 22:57
  • $\begingroup$ "$y \not \in \{x\}$"then shouldnt $y \in \{x\}^c$ and hence $f(y) \in \{f(\{x\}^c)$? $\endgroup$ – Olba12 Jan 29 '16 at 22:59
  • $\begingroup$ Yes. And thus means $f(y)\ne f(x).$ Since this holds for any $x,$ $f$ must be injective. $\endgroup$ – mfl Jan 29 '16 at 23:01
  • $\begingroup$ Okey, but you wrote $f(y) \in \{f(x)\}^c$ , I think it should be $f(y) \in f(\{x\}^c)$ $\endgroup$ – Olba12 Jan 29 '16 at 23:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.